STUDI PENGARUH PENGENDALI ATC TERHADAP KOMPONEN TEKNOLOGI DALAM SISTEM ATC - Tranggono Tranggono; Rusindiyanto Rusindiyanto (Jurnal Ilmiah Dinamika Teknik, 2019)
Air Traffic Controller is one profession with special and complex level of expertise. This is because an ATC controller has activities that involve mindset, communication, decision making, interaction and relationships between human-computers that are vulnerable to errors. And it has a very high risk because it deals with the safety of many people. The task of an ATC controller is to maintain a safe distance between planes that have variations with the density of traffic and airspace. This study aims to determine the relationship between ATC (humanware) controllers and technological components in ATC systems, among others: Organization (orgaware), software (infoware) and equipment / machinery (technoware) of ATC equipment. To identify and know the relationship between variables, with Partial Least Square (PLS). Based on the t-statistical value, obtained significant influential factors indicating the existence of a relationship between the ATC controller (humanware) and other system components (infoware, orgaware, and technoware).